Energy poverty and deprivation in Ireland - Michelle Barrett; Niall Farrell; Barra Roantree (The Economic and Social Research Institute (ESRI), 2022)
This report - funded by the Community Foundation for Ireland - explores the issue of energy poverty and deprivation in Ireland, once again to the forefront of the policy debate given recent increases in energy prices.
Keywords: 330; Energiekonsum; Energiepreis; Inflation; Konsumentenverhalten; Haushaltsökonomik; Armut; Risiko; Energiepolitik; Irland